Ethnomathematical investigation of traditional games for cultural preservation in the Indonesia-Timor Leste border region - Deda, Yohanis Ndapa; Disnawati, Hermina (Journal of Honai Math, 2024)
Traditional games offer children numerous benefits, including health, character development, and educational resources. However, these games have yet to be explored as learning tools for students with dyscalculia, particularly in border areas. This research aims to investigate the mathematical concepts embedded in traditional games as part of the local culture in the Indonesia-Timor Leste Border Area (ITLBA) community. Employing an exploratory approach with an ethnographic methodology, the study utilized documentation, observation, and interviews involving 13 children aged 7-14 years and five informants from the border area. Findings revealed mathematical concepts, including geometry and numerical concepts, within traditional games such as Galah Asin, Kelereng, Siki Doka, and Congklak. Moreover, these games instilled character values such as patriotism and sportsmanship. Children in the ITLBA region benefited from traditional games through social interaction, fostering kinship, cooperation, responsibility, and enhancing psychomotor skills. Ethnomathematics research on traditional games at ITLBA suggests utilizing these games as a platform for mathematics education, especially for students with disabilities. Leveraging classic games can help bridge the gap for students with disabilities, facilitating their numerical skills development within the educational context.